Multiphase sinusoidal oscillators using translinear current conveyors and only grounded passive components - Loescharataramdee, C.; Kiranon, W.; Sangpisit, W.; Yadum, W. (My University, 2001)
A generalized multiphase sinusoidal oscillator is presented. The circuit realization uses the translinear bipolar second generation current-controlled conveyors to generate arbitrary n current signals equally spaced in phase. The proposed circuit consists of n multi-output current controlled conveyors and a current amplifier connected in cascade. The only passive component employed in each of the n conveyors is one grounded capacitor. The oscillation condition and oscillation frequency are independently controlled. The former depends only on the number of the phase signals of the oscillator. The dependency of the latter on the input resistance of the input ports of the current conveyors makes electronic tunability possible using the bias currents. The circuit also enjoys having simple structure and very low component count and it is highly suitable for monolithic implementation.
Keywords: Circuits; Frequency; Joining processes; Oscillators; Thermal resistance; Transfer functions; Voltage